A global space–based approach for wide strip flank milling of freeform surface with a barrel cutter. Issue 1 (2nd January 2019) - Wang, J.; Luo, M.; Zhang, D. H.
ABSTRACT: Due to the wide contact area between the tool and the machining surface in flank milling, the engagement relationship between them cannot be well described by the local differential property of the surface. In terms of this problem, a new global space based approach is presented to realise the path planning for wide strip flank milling with barrel cutter. Firstly, the method for calculation of the global space in machining process is given through the analysis of the engagement relationship between the barrel cutter and the machined surface, and the error in the global space is analysed. Secondly, the maximum strip width–based optimisation of tool axis is established combining with the engagement relationship, and the corresponding tool orientation and feed direction are determined. Thirdly, by establishing the maximum strip width vector field in the parameter domain and combining the stream function to determine the initial toolpath, the path planning of the flank milling with the barrel cutter is achieved. Finally, the developed algorithm is validated by geometrical simulation and comparing with existing methods.